N-Acetylcysteine Supplementation Reduces Oxidative Stress and DNA Damage in Children with beta-Thalassemia - KOÇ, AHMET (TAYLOR & FRANCIS LTD, 2014)
There are several reports that increased oxidative stress and DNA damage were found in beta-thalassemia major (beta-TM) patients. In this study, we aimed to evaluate the effects of N-acetylcysteine (NAC) and vitamin E on total oxidative stress and DNA damage in children with beta-TM. Seventy-five children with transfusion-dependent beta-thalassemia (beta-thal) were randomly chosen to receive 10 mg/kg/day of NAC or 10 IlEkg/day of vitamin E or no supplementation; 28 healthy controls were also included in the study. Serum total oxidant status (TOS) and total antioxidant capacity (TAC) were measured, oxidative stress index (OSI) was calculated, and mononuclear DNA damage was assessed by alkaline comet assay; they were determined before treatment and after 3 months of treatment. Total oxydent status, OSI, and DNA damage levels were significantly higher and TAC levels were significantly lower in the thalassemic children than in the healthy controls (p<0.001). In both supplemented groups, mean TOS and OSI levels were decreased; TAC and pre transfusion hemoglobin (Hb) levels were significantly increased after 3 months (p <0.002). In the NAC group, DNA damage score decreased (p = 0.001). N-acetylcysteine and vitamin E may be effective in reducing serum oxidative stress and increase pre transfusion Hb levels in children with beta-thal. N-acetylcysteine also can reduce DNA damage.
Keywords: beta-Thalassemia (beta-thal); child; DNA damage; N-acetylcysteine (NAC); oxidative stress; vitamin E; ANTIOXIDANT STATUS; IRON; ERYTHROCYTES; DEPLETION; OXIDANT; PLASMA; CELLS; LDL